A lifestyle intervention randomized controlled trial in obese women with infertility improved body composition among those who experienced childhood adversity. (18th August 2020) - van Dammen, Lotte; Bush, Nicole R.; de Rooij, Susanne; Mol, Ben Willem; Mutsaerts, Meike; van Oers, Anne; Groen, Henk; Hoek, Annemieke; Roseboom, Tessa
Abstract: Previous research indicates that tailoring lifestyle interventions to participant characteristics optimizes intervention effectiveness. Our objective was to assess whether the effects of a preconception lifestyle intervention in obese infertile women depended on women's exposure to adversity in childhood. A follow‐up of a preconception lifestyle intervention randomized controlled trial (the LIFEstyle study) was conducted in the Netherlands among 577 infertile women (age 18–39 years) with a body mass index (BMI) ≥29 kg/m 2 at time of randomization; N = 110 (19%) consented to the follow‐up assessment, 6 years later. A 6‐month preconception lifestyle intervention aimed weight loss through improving diet and increasing physical activity. The control group received care as usual. Outcome measures included weight, BMI, waist and hip circumference, body fat percentage, blood pressure and metabolic syndrome. The potential moderator, childhood adversity, was assessed with the Life Events Checklist‐5 questionnaire. Among the 110 women in our follow‐up study, n = 65 (59%) reported no childhood adverse events, n = 28 (25.5%) reported 1 type of childhood adverse events and n = 17 (15.5%) reported ≥2 types of childhood adverse events. Regression models showed significant interactions between childhood adversity and effects of lifestyle intervention at the 6‐year follow‐up. Among women who experienced childhood adversity, the intervention significantly reduced weight (−10.0 [95% CI −18.5 to −1.5] kg, p = 0.02), BMI (−3.2 [−6.1 to −0.2] kg/m 2, p = 0.04) and body fat percentage (−4.5 [95% CI −7.2 to −1.9] p < 0.01). Among women without childhood adversity, the intervention did not affect these outcomes (2.7 [−3.9 to 9.4] kg, p = 0.42), (0.9 [−1.4 to 3.3] kg/m 2, p = 0.42) and (1.7 [95% CI −0.3 to 3.7] p = 0.10), respectively. Having a history of childhood adversity modified the effect of a preconception lifestyle intervention on women's body composition. If replicated, it may be important to consider childhood adversity as a determinant of lifestyle intervention effectiveness.